2019
DOI: 10.3390/ijerph16122192
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Sugar-Sweetened Beverages Has a Dose-Dependent Effect on the Risk of Non-Alcoholic Fatty Liver Disease: An Updated Systematic Review and Dose-Response Meta-Analysis

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is a serious health problem, but the dose-response relationship between sugar-sweetened beverages (SSBs) and NAFLD remains uncertain. Methods: A systematic review and dose-response meta-analysis were conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Review Manager 5.3 and Stata 14.0 were used to combine trials and analyze data. The dose-response meta-analysis was performed by non-linear trend reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 37 publications
5
64
1
5
Order By: Relevance
“…risk of NAFLD increased at least 26%, and up to 53% in patients who drank at least 1 cup per day [27]. This reiterates the importance of educating and fostering of healthy dietary patterns in the primary prevention of NAFLD.…”
Section: Plos Onementioning
confidence: 74%
See 1 more Smart Citation
“…risk of NAFLD increased at least 26%, and up to 53% in patients who drank at least 1 cup per day [27]. This reiterates the importance of educating and fostering of healthy dietary patterns in the primary prevention of NAFLD.…”
Section: Plos Onementioning
confidence: 74%
“…Indeed, a recent systematic review and meta-analysis demonstrated that sugar-sweetened beverage consumption significantly increased the risk of NAFLD in a dose-dependent fashion. At a quantity of at least 1 cup per week (moderate-high dose), the relative risk of NAFLD increased at least 26%, and up to 53% in patients who drank at least 1 cup per day [ 27 ]. This reiterates the importance of educating and fostering of healthy dietary patterns in the primary prevention of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The preservation of systemic insulin responsiveness (and glucose tolerance; Supplementary Figure 2) in our model demonstrate a clear decoupling of the mechanisms responsible for steatosis and those responsible for impairments in insulin sensitivity following chronic sucrose intake and, in the case of female mice, overt obesity ( Figure 1A). In humans, sugar sweetened beverage consumption is strongly associated with NAFLD (Arenaza et al, 2019;Asgari-Taee et al, 2019;Assy et al, 2008;Cahlin et al, 1973;Chen et al, 2019;Ma et al, 2015) but not always with obesity (Te Morenga et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from observational studies and meta analyses indicate that excessive sugar intake or compromised sugar metabolism may be an initiating factor for NAFLD in humans (Arenaza et al, 2019;Asgari-Taee et al, 2019;Assy et al, 2008;Cahlin et al, 1973;Chen et al, 2019;Ma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation